Mathematical Modelling of Population Dynamics with Growth Sensitivity of Abuja Federal Territory, Nigeria - Akaligwo, Emmanuel (Journal of Statistical Modeling and Analytics (JOSMA), 2025)
Keeping track of the human population is essential for proper planning for facilities such as healthcare, infrastructure, education, and other essential needs. There are various ways by which the government can ensure that service provision is improved and maintained for its citizens and very often this starts by knowing the changes in demography as a function of time. In this work, mathematical modeling and simulations are used to study the population dynamics of Abuja. The models are used for prediction of the population and how its dynamics change over time. With approximate growth rate at 9.3% per annum, the projected population of Abuja will hit 30,220,701 million by the year 2039 all things being equal. Parameter sensitivity analysis was performed using population census data, and the results show a huge influence of variations in the model parameters. The results indicate that the difference between the per capita birth and death rate parameters is crucial for changes in the population. Such findings can also be analogously applied to other cities with a similar population structure and economy.